If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -19 = 3n + 13 Reorder the terms: -19 = 13 + 3n Solving -19 = 13 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. -19 + -3n = 13 + 3n + -3n Combine like terms: 3n + -3n = 0 -19 + -3n = 13 + 0 -19 + -3n = 13 Add '19' to each side of the equation. -19 + 19 + -3n = 13 + 19 Combine like terms: -19 + 19 = 0 0 + -3n = 13 + 19 -3n = 13 + 19 Combine like terms: 13 + 19 = 32 -3n = 32 Divide each side by '-3'. n = -10.66666667 Simplifying n = -10.66666667
| 0.5=-2x+8.1 | | 25m+40=240 | | 77=7(m+4) | | 2f(-4)=5x-5 | | 8x+5-10x=-6-x | | x+10+x+(3x-5)=180 | | 38=3x+y | | (3y-7)+(-4y-8)= | | 40.000+1.000x=60.000 | | 1.12x-2/4 | | 1-7/12-3/4 | | 19/.75 | | 5x-2x+2x=-5-8+1 | | 40.000+1.000=60.000 | | 67+x=282 | | -12+4x=6x-32 | | -4(2y+3)=(-18) | | 6/7y=9/14 | | -30=13x-80 | | 3/8k=3/4 | | x+2x+5+4x-7=0 | | 14=-2(x-3)+4 | | 8-7y=-34 | | -1/4x+15=-5 | | 3a+4b+2c=40 | | 9+(-4)x=13 | | -2(y-2)+3(4+3y)=-5 | | 9x^2+6=3x | | -2lx+3l=-60 | | 2xsquared+4x=0 | | 4b+18+3b=74 | | -54-9b-2b=-10 |